Fabrication of Nanocomposite Scaffolds Including Metal Nanoparticles for Tissue Engineering Applications - Ayşen Aktürk; Cagkan Alemdar; Emre Ekmen; İrem Keskin; Nagihan Tunca; Melek Erol Taygun; Sadriye Kücükbayrak (Journal of Chemical Engineering Research Updates, 2017)
This study presents the findings of a research on fabricating composite nanofibrous mats including silver and copper nanoparticles for tissue engineering applications. For this purpose, two different types of silver nanoparticles (soluble starch capped silver nanoparticles, sodium alginate capped silver nanoparticles) and two different types of copper nanoparticles (soluble starch capped copper nanoparticles, sodium alginate capped copper nanoparticles) were successfully incorporated into polyvinyl alcohol (PVA) fibers through electrospinning process. Characterization studies with x-ray diffraction (XRD), scanning electron microscope (SEM) and Fourier transform infrared spectroscopy (FTIR), inductively coupled plasma spectrometer (ICP) were conducted to determine physical and structural properties of the obtained nanofiber mats. According to SEM analysis it was observed that interconnected and randomly-oriented nanofibers were successfully generated. Additionally, XRD and FTIR studies proved the existence of silver nanoparticles and hydroxapatite on the nanofiber mats immersed in simulated body fluid (SBF) for 7 days. The results indicated that long term silver ion release was achieved. Overall results showed that these nanofibrous mats can be good candidates as multifunctional scaffolds for tissue engineering applications.